Study on end brush deburring and sintered diamond ball deburring of micro-features milled - Sai, T. K.; Saptaji, Kushendarsyah; Gebremariam, M.A.; Fatchurrohman, Nanang (IOP Publishing, 2019)
The presence of top burr in the micro-features produced by milling process can deteriorate and affect the surface quality of the products. Though there are some deburring methods can be used and reported successfully remove the burr in the micro scale features, however simpler and alternative method is still needed. Two of the deburring methods that can be used are end brushing and sintered diamond ball methods. Therefore the aim of this paper is to study the application of the end brush and sintered diamond ball for deburring top burrs exist on micro features produced by milling process. Slot milling experiments were conducted and subsequently deburring process using the two methods was conducted. Micro scale features were also produced using milling process followed by deburring. The deburred results were observed visually using optical microscope and Scanning Electron Microscope (SEM) and average surface roughness was measured. Experimental results show that the end brush and sintered diamond ball deburring have successfully remove the top burrs. The end brush deburring method produced better surface quality compared to the sintered diamond ball.